Create and deliver a killer product demo : tips and tricks to wow your customers - Santolalla, Oscar (Apress, 2019)
Create great product demos and sell more of your product with the strategies and inspiration in this book. Insightful interviews are presented with professionals who are giving killer product demos in several types of businesses today. The strategies taught in this book are based on the analysis of product demos that made history and brought millions to their companies (Apple, Intel, Microsoft, Tesla, and more). Every day thousands of companies give demos to sell their products. In pre-sales for enterprise software a bad demo can make your product look too complex to the point where decision makers won't buy it. In Software-as-a-Service (SaaS) you need to quickly convert signups into active and paying users. At a product launch event you want a perfect demo that is both persuasive and memorable. Remember Steve Jobs? What You'll Learn: Apply a simple step-by-step method to create effective product demonstrations Know the 5 steps to create a wow moment Study the first exhaustive analysis of product demos that made history: Douglas Engelbart's Mother of All Demos; Steve Job's Macintosh, iPod, and iPhone; and many more Avoid common mistakes and maximize your presence as a technical presenter Align your demo with your sales process in enterprise software, Software-as-a-Service (SaaS), mobile apps, etc. Be aware of trends in technology for product demos.